Applying RF current harmonics for end-point detection during etching multi-layered substrates and cleaning discharge chambers with NF3 discharge - Lisovskiy, V.; Booth, Jean-Paul; Landry, K.; Douai, D.; Cassagne, V.; Yegorenkov, V. (www.elsevier.com/locate/vacuum, 2007)
The present paper reports the results of studying the characteristics of the etching process of multi-layered materials (Si3N4/SiO2/Si and SiO2/Si) and of cleaning technological chambers covered with silicon nitride films (Si3N4) in a NF3 RF capacitive discharge. The process of chamber cleaning was monitored with a mass spectrometer. The gas pressure, RF voltage amplitude, current–voltage phase shift, ohmic current as well as the second harmonic of the RF current were also recorded. The opportunity of using these parameters for end-point detection of etching and plasma cleaning is discussed. It is found that the second harmonic of the RF current may be successfully used for end-point detection of multi-layered materials etching and to monitor the cleaning process of technological chambers. The cleaning of chambers of complicated design may possess a double-stage pattern.
Keywords: plasma physics; gas discharges